Organized Labour and Local Politics: Ontario's 2006 Municipal Elections - Savage, Larry (Labour / Le Travail, 2008)
The article provides information on the municipal elections which were held in Ontario in November 2006. The elections represented a strategic shift in the political priorities of organized labour. The Canadian Labour Congress (CLC) held a series of strategy sessions, candidate schools, public speaking and media courses, and political organizer training sessions. The campaign was rolled out in four phases including visioning, training and endorsement, and accountability.
Keywords: CANADIAN Labour Congress; LOCAL elections; Labor Unions; Ontario; POLITICAL campaigns; POLITICAL endorsements